Knowledge and Practice of Injection Safety among Nurses Working in Tertiary Health Science Institute of Eastern Nepal - Rayamajhi, Sarobara; Thapa Pachya, Ambika (Journal of Karnali Academy of Health Sciences, 2023)
Background: Unsafe injections occur routinely in most developing world regions, implying a significant potential for the transmission of blood-borne pathogens. Unsafe injections account for a significant proportion of all new hepatitis B and C infections. This study explores the factors affecting knowledge and practices and to carry out observations in selected sample.Material and Methods: A descriptive cross-sectional study design was conducted among 143 nurses working at selected wards of BPKIHS using a self-administered questionnaire from nurses of the Medical, Surgical, Emergency, Orthopedic, ICU, SICU, Gynecology, Antenatal, and Postnatal wards. The nurses were selected using population-proportionate stratified random sampling. Observation of the 30 injection procedure was carried out. The data was analyzed using descriptive and inferential statistics.Results: The mean age of the respondents was 25.48±3.66 years. Poor knowledge was seen among 33.6%, and good knowledge was seen among 66.4% of the respondents. Similarly, good practice was observed among 11.2% and excellent practice was observed among 88.6% of the respondents. Significant association was found between knowledge and total work experience (p 0.023), vaccination against hepatitis B (p